Can canola meal and soybean meal be used as major dietary protein sources for kuruma shrimp, Marsupenaeus japonicus? - Mahbuba, Bulbul; Kader, Md Abdul; Asaduzzaman, Md.; Ambak, Mohd. Azmi; Khan Chowdhury, Ahmed Jalal; Hossain, Md Sakhawat; Ishikawa, Manabu; Koshio, Shunsuke (Elsevier B.V., 2016)
A feeding trial was conducted to utilize canola meal and soybean meal as major dietary protein sources for kuruma shrimp, Marsupenaeus japonicus. Four isocaloric diets (19 kJ g−1) were formulated by reducing 0 (FM40), 70 (FM12), 85 (FM6) and 100% (FM0) of dietary fishmeal with a combination (4:6) of canola meal and soybean meal (blend). Based on a series of previous studies, all the plant protein diets (FM12, FM6 and FM0) were supplemented with 1.00% lysine, 0.50% methionine, 0.04% phytase and varying levels of fish soluble to improve the nutritional quality of the diets. Fifteen shrimp with an initial average weight of 1.74 g were randomly stocked in 12, 54 l rectangular tanks in triplicate per dietary treatments. The shrimpwere given the respective test diets daily by hand at 8–10% of body weight for 60 days. Final bodyweight (g) and specific growth rate (% day−1) were not significantly (P N 0.05) affected by reducing fishmeal with plant protein blend. Feed intake was also not varied among the dietary treatments. On the other hand, feed conversion ratio was significantly (P b 0.05) increased in the FM0 group, while no difference was found among the rests. Protein efficiency ratio had an opposite trend and the FM0 group demonstrated significantly lowest value. Similarly, protein gain (g kg weight gain−1) and protein retention (%) were significantly decreased in the FM0 group. Dietary treatments had no negative effects (P N 0.05) on the whole body composition. Significant effect was also not found on the protease activity (unit mg−1 protein) in the digestive tract of shrimp fed the FM40, FM12 and FM6 diets, while the value was significantly decreased in shrimp fed the FM0 diet. The values for the total hemocyte count (cells ml−1) and viable cells (%)were lowest in the FM0 group, however these parameterswere not significantly varied among the dietary treatments. Upon considering the results obtained in the present experimental condition, it has been concluded that canolameal and soybean meal could be effectively utilized as major protein sources by kuruma shrimp. The dietary fishmeal could be reduced to only 6% (85% replacement) with a blend of canola meal and soybean meal, and supplementation of methionine, lysine, phytase and fish soluble without compromising growth, feed utilization, body composition and health of juvenile kuruma shrimp.